Shaping the Victim: Borders, security, and human trafficking in Albania - Campbell, James (Anti-Trafficking Review, 2013)
Borders are productive sites where knowledge is gathered and migrant populations are formed. The knowledge gathered from victims of trafficking reinforces a victim narrative that represents a perceived threat to society by highlighting violence, criminality, coercion, and naivety. Using Albania as a case in point, the article looks at trafficked people and the narratives of victimhood that surround them. In the case of trafficked people, the border projected out towards other states produces a discursively defined victim of trafficking. When projected back within the national territory, the border essentially produces a criminalised sex worker. To argue this point, the article discusses the role victims of trafficking play in the EU and looks at how international norms espoused by the OSCE and IOM have prepped the Albanian border for EU ascension and created the means for governable populations within Albania.